The Urgency of the Newest Renewable Energy Law in International Law Perspective - Mujamil, Muhamad Haikal; Fathurrohman, Fahmi; Monitasari, Restu Gusti (Tirtayasa Journal of International Law, 2023)
The research results indicate that global society's culture desires the use of sustainable energy, as evidenced by numerous international agreements on renewable energy and environmental management. It is important for Indonesia to create a conducive legal framework for the use of sustainable energy and environmental management while fulfilling its obligations as a member of international law. The research problem is that the energy demand in Indonesia is currently increasing due to significant economic growth. The increasing energy demand, on the other hand, requires Indonesia to comply with the ratification of sustainable energy use and environmental management. One of the main obstacles is the lack of strong and consistent regulations. This research uses a normative juridical method with secondary data. Secondary data was collected through searches and literature studies based on primary, secondary, and tertiary legal materials, and qualitative data analysis techniques were used to help researchers understand the phenomena being studied and describe various perspectives descriptively.